Atypical event-related potentials revealed during the passive parts of a Go-NoGo task in autism spectrum disorder: a case-control study - Anne L. Høyland; Terje Nærland; Morten Engstrøm; Tonje Torske; Stian Lydersen; Ole A. Andreassen (Molecular Autism, 2019)
Abstract Background The core features of autism spectrum disorder (ASD) are easily recognizable in non-structured clinical and real-life situations. The features are often difficult to capture in structured laboratory settings, and the results from tests do not necessarily reflect symptom severity. We investigated neurophysiological processing in the passive parts of a cued Go-NoGo task, using the active parts of the test as a comparator. Methods Forty-nine adolescents diagnosed with ASD and 49 typically developing (TD) adolescents (age 12–21 years) were included. Daily life executive function was assessed with the Behavior Rating Inventory of Executive Function (BRIEF). We applied a visual cued Go-NoGo task and recorded event-related potentials (ERPs). We investigated occipital N1, a component related to early perception of visual stimuli, and P3a, a fronto-central component related to switching of attention, in the passive and active parts of the test. Results During the passive parts, the ASD group had statistically significantly longer N1 latency (p < 0.001, Cohens d = 0.75) and enhanced amplitude of P3a (p = 0.002, Cohens d = 0.64) compared to the TD, while no significant differences were observed in the active parts. Both components correlated significantly with the Behavioral Regulation Index of the BRIEF (partial correlation r = 0.35, p = 0.003). Conclusion Delayed N1 response, indicating altered visual perception, and enhanced P3a response, indicating increased neural activation related to attention allocation, were found during the passive parts of a Go-NoGo task in ASD participants. These abnormal ERP signals in the non-structured settings were associated with everyday executive function, suggesting that neurophysiolocal measures related to atypical control of alertness and “hyper-awareness” underlie daily life dysfunction in ASD. Assessments during passive settings have a potential to reveal core neurobiological substrates of ASD.